Evaluation of car accident parameters during collision - Tautkus, Arūnas; Jurkauskas, Algirdas (Transport, 2002)
According to he literature source [5], almost 47–52% from all carcrashes make collisions of cars. So it is possible to conclude that almost each second a carcrash is a collision. One of the most important parameters that should be determined during carcrash investigation is the car speed before the accident. Calculation of the parameters in various situations differs. The experts performing the investigation work of car crashes improve or create carcrash investigation methods in various cases. The methods of speed determination before crashes arc presented in these cases: direct collision, when cars move one after another, direct sided collision and sided sliding collision as well. First Published Online: 19 Dec 2011